2006
DOI: 10.1099/mic.0.28679-0
|View full text |Cite
|
Sign up to set email alerts
|

Water channels are important for osmotic adjustments of yeast cells at low temperature

Abstract: The importance of aquaporin expression in water permeability in Saccharomyces cerevisiae was assessed by measuring the osmotic water permeability coefficient (P f ) and the activation energies (E a ) from both hypo-and hypertonic experiments performed with whole protoplasts from four strains differing in aquaporin level of expression: parental, double-deleted and overexpressing AQY1 or AQY2. Double-deleted (lower P f ) and AQY1-overexpressing strains (higher P f ) presented linear Arrhenius plots with E a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
4
28
0
1
Order By: Relevance
“…When human red cells were treated with pchloromercuribenzosulfonic acid to block proteinaceous water transport, similar high osmotic permeability (20 μm/s, Macey et al 1972;Macey and Farmer 1970) was observed. By contrast, protoplasts of yeast mutants, harboring no aquaporin (AQP) capable of water transport, revealed P f values of only 2 μm/s at 23°C (Soveral et al 2006). Together, these results point toward the importance of lipid composition for water permeability of biological membranes in addition to temperature (Finkelstein 1976;Krylov et al 2001;Lande et al 1995;Kleinhans 1998;Redwood and Haydon 1969).…”
Section: Permeability Of Fungal Cell Wallsmentioning
confidence: 99%
“…When human red cells were treated with pchloromercuribenzosulfonic acid to block proteinaceous water transport, similar high osmotic permeability (20 μm/s, Macey et al 1972;Macey and Farmer 1970) was observed. By contrast, protoplasts of yeast mutants, harboring no aquaporin (AQP) capable of water transport, revealed P f values of only 2 μm/s at 23°C (Soveral et al 2006). Together, these results point toward the importance of lipid composition for water permeability of biological membranes in addition to temperature (Finkelstein 1976;Krylov et al 2001;Lande et al 1995;Kleinhans 1998;Redwood and Haydon 1969).…”
Section: Permeability Of Fungal Cell Wallsmentioning
confidence: 99%
“…The aquaporin-encoding genes in S. cerevisiae (AQY1 and AQY2) contain inactivating mutations in most laboratory strains, and only AQY1 encodes a functional water channel in most natural isolates and industrial strains (2,3). In strains with altered expression of these genes, a significant role for yeast aquaporins restricted to low temperatures has been found (5).…”
mentioning
confidence: 99%
“…Light scattering stopped-flow methodologies have been used to measure osmotic water permeability (P f ) in several systems, including yeast protoplasts and vesicles (4,5,8,10), but they were not successful when they were used with intact yeast cells (data not shown). With protoplasts, equivalent P f values were obtained using two different stopped-flow techniques, light scattering and fluorescence (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations